(untitled) (Politeja, 2020)
The Past and the Future of Memory Research. Do We Need a New Discipline? The article discusses the status of memory studies as an academic discipline as well as their complex terminology and methodology. The author focuses on examples from Poland and Germany, arguing that in spite of many initiatives, such as academic associations or academic journals, memory studies are an interdisciplinary field rather than an academic discipline. The term ‘memory’ is usually used as a metaphor or analytical tool instead of being the actual object of research. The current popularity of historical issues in the public sphere requires a more precise and disciplined approach to the topic.